ILLOCUTIONARY AND PERLOCUTIONARY ACTS ON MAIN CHARACTERS DIALOGUES IN JOHN MILNE’S NOVEL: “ THE BLACK CAT” - Dwi Astuti Wahyu Nurhayati; Yuwartatik Yuwartatik (IJOTL-TL: Indonesian Journal of Language Teaching and Linguistics, 2016)
This article describes the types of illocutionary acts and the impact of perlocutionary acts on main characters’ dialogues in John Milne’s Novel: The Black Cat”. This study used descrpitive qualitative design. Data of this study were  dialogues in the “The Black Novel”. The study revealed that the dialogue posses five types of illocutionary acts i.e. declaratives, assertives, expressive, directives, commissives and the impact of perlocutionary act. Readers can broaden and enrich the knowledge of speech acts especially Illocutionary, perlocutionary acts;  understand what the speaker intends and know the sequence of events in speaker utterances; practice strategies of speech act in their daily life, and use literary works to learn language naturally.